Cuticular hydrocarbon of pupal cases of chrysomya megacephala (fabricius) and its possible use for estimating postmortem interval - Nurul Nadhirah Nasir, author; Naji Arafat Mahat, supervisor; Jaafariah Jaafar, supervisor; Reena Abd. Rashid, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains) - Universiti Teknologi Malaysia, 2017.